Apparently novel genetic syndrome of pachygyria, mental retardation, seizure, and arachnoid cysts - BAYRAKLI, FATİH (WILEY-LISS, 2007)
We report on an apparently new syndrome in a consanguineous family with seven members, three of whom have cerebral anomalies including pachygyria and arachnoid cysts along with mental retardation and seizures. The two patients with seizure disorders also had multiple enlarged perivascular spaces seen in the white matter of the centrum semiovale. Our data provide a contribution to the acacumulating knowledge on familial cerebral anomalies including arachnoid cysts and lissencephaly. Given the lack of mutation in known lissencephaly genes such as LIS1, 14-3-3 epsilon, and DCX, this syndrome may constitute a new phenotype with autosomal recessive inheritance.(c) 2007 Wiley-Liss, Inc.
Keywords: lissencephaly; genetics; arachnoid cysts; mental retardation; pachygyria; neuronal migration defects; pachygyria; seizures; NEURONAL MIGRATION DISORDERS; POLYCYSTIC KIDNEY-DISEASE; MIDDLE CRANIAL FOSSA; CAVERNOUS MALFORMATIONS; CEREBELLAR HYPOPLASIA; CHILDREN; SIBLINGS; ASSOCIATION; MUTATIONS; EPILEPSY